Semantic Types of Subjects and Objects of the Verb LIE in American Corpus (COCA) - Elvi Citraresmana (Universitas Teknokrat Indonesia, 2019)
This research discusses semantic types of subjects and objects of the verb lie and the phenomena of the usage of verb in American Corpus (COCA) from 1990 to 2012. This research describes the subjects who told lies frequently and the objects who received the lies from the subjects and what topics American usually had when they lied. The verb lie has two meanings, they are ‘not telling the truth’ and ‘to recline or lie down’. In this research, the verb lie refers to the meaning of ‘not telling the truth’. The corpus does not divide between those two meanings, so the writer collected and divided them manually. After that, the prospective ones were categorized based on frequency (F) in the highest, moderate, and low levels to be analyzed using descriptive-empirical method which is based on the speakers’ experiences. This was done to analyze and formulate the semantic types of the subjects of the verb ‘lie’ and the semantic types of the objects of the phrasal verb ‘lie to’ and ‘lie about’ during the period of 1990 until 2012. The theories are based on the corpus linguistics theory suggested by Firth (1957), Jones and Sinclair (1974), Sinclair et al. (2004), Cowie (1981, 1994) and Cowie et al. (1993), Stubbs (2002), Nesselhauf (2004), McEnery and Hardie (2001, 2012). For the semantic types, this research refers to the theory of Sinclair (1991), Stubbs (2001), Dixon (2005), McEnery and Hardie (2012), and Hanks (1987, 2013). Lindquist (2009) inspired by Palmer (1933) proposes the adjacent collocation. The book published by Bureau of International Information Programs. U.S. Department of State (2005) was used in order to analyze the correlation between the phenomena of telling lies in America. The results of analysis show that the semantic types of the subjects are the subject as human, human group, human institution, and social group. The semantic types of the objects of phrasal verb of ‘lie to’ are institution, social group, and social human, human, human group. The semantic types of the objects of phrasal verb ‘lie about’ are social event, human action, human activity, and various things.Keywords: Adjacent collocation, corpus linguistics, frequency, semantic type